อุทกพลศาสตร์ของช่วงการไหลในเครื่องปฏิกรณ์ฟลูอิไดซ์เบดแบบหมุนเวียนสองมิติ - สุทธิชัย บุญประสพ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Circulating fluidized bed reactors are widely used in many industries such as combustor, coal gasifier and fluid catalytic cracking reactors. Bubbling and turbulent fluidizations can provide high density bed in a riser, but they cannot be used in continuous processes. The circulating fluidization, which are fast fluidization and pneumatic transport, is in dilute phase leading to low efficiency in operation. Therefore, searching for the new fluidization regime receives attention. The transient flow behavior in two-dimensional plexiglas riser with 2.00 m height, 0.15 m width and 0.05 m depth was investigated using CCD camera system. Air at room temperature was selected as the fluid phase. Silica sand and polyvinyl chloride particles were selected to use as the solid phase. The results expressed both vertical and radial solid particle velocity profiles. It was found that the velocity profile of vertical solid particles in freeboard region of turbulent fluidization regime was uniformly distributed with positive values even at the near riser wall region. This behavior was similar to circulating turbulent fluidization regime with double stage air feeding system. Circulating turbulent fluidization regime can be found in the high solid recirculating rate and low superficial gas velocity comparing to the transport velocity. The results can be used to improve the design of circulating fluidized bed reactor and to validate the mathematical model in the future.